Politik Kepala Daerah Perseorangan Memperbesar Kekuasaan - HUSNUL ISA HARAHAP (Universitas Sumatera Utara, 2013)
This is a study about the political of regional head to strengthen the power. This study is using political system approach. Data collection is using field study techniques and literature (method interviews, library research (library research) and study documents. Analysis is using qualita-tive technique, especially descriptive analysis method. The finding of this study is the head of the region have a tendency to magnify its power. There is no execption to the regional head which is the individual candidates. This is because in politics, great powers it needed to run and maintain power. In the case in Kabupaten Batubara, efforts to to strengthen the power can be seen from the success of OK Arya Zulkarnain gaining a strategic position in a political parties. OK Arya Zulkarnain joined the Golkar Party and also became Chairman of DPD Kabupaten Batubara of the Golkar Party period (2010-2015). So the influence of OK Arya Zulkarnain in parliament becomes larger. Especially in influencing policy at the local legislature (DPRD Kabupaten Batubara).Keywords: Power, political of regional head, political parties.